Physical Performance Changes in Season are Associated with GPS Data in Soccer Players - Zandavalli, Laura A.; Grazioli, Rafael; Izquierdo, Mikel; Garcia-Tabar, Ibai; Veeck, Filipe; Setuain, Igor; Ramirez, Giovanni S.; Aroni, André L.; Pinto, Ronei Silveira; Cadore, Eduardo L. (International Journal of Sports Medicine, 2024)
This study investigated the associations between pre-season and in-season performance with external workload in professional soccer players. Twenty-one players completed hamstring strength, countermovement jump (CMJ), 20-m sprint, and Yo-Yo intermittent recovery tests before (pre-season) and after 8 weeks (in-season). External workload (total distance, high-intensity running distance, number of sprints, and power plays) was quantified during this period, and used to divide the average above and below subgroups outcome by outcome for further analyses. Significance was accepted when P≤0.05. Hamstring strength declined from pre- to in-season [− 6%; p=0.014; effect size (ES): − 0.41], while Yo-Yo performance improved (46%; p=0.001; ES: 1.31). When divided by high-intensity running distance, only the below-average subgroup improved CMJ performance (5%; p=0.030). For minutes played, the above-average subgroup improved Yo-Yo performance (41%; p<0.001), but not the below-average subgroup. Furthermore, playing time correlated with improved Yo-Yo performance (p=0.040; r=0.534). Improved 20-m sprint performance associated with more sprints performed (p=0.045; r=− 0.453). Physical capabilities changed over a competitive season and were related to, and differentiated by, external workload. Because hamstring strength decreased and CMJ only improved in players exposed to less high-intensity external load, practitioners should individualize approaches to counteract these conditions when high external workload is performed over the season.
Keywords: game analysis; performance; strength; team sport; testing